Intimate Partner Violence : Economic Costs and Implications for Growth and Development - Duvvury, Nata; Callan, Aoife; Carney, Patrick; Raghavendra, Srinivas (World Bank, Washington, DC, 2014)
Violence against women, recognized globally as a fundamental human rights violation, is widely prevalent across high-, middle-, and low-income countries. Violence against women has significant economic costs in terms of expenditures on service provision, lost income for women and their families, decreased productivity, and negative impacts on future human capital formation. The paper makes a major contribution to the discussion of economic implications of intimate partner violence (IPV) through its conceptual mapping of the links between IPV and economic growth based on a review of literature on their complex dynamics based on data from Vietnam. It reviews costing methodologies and identifies types of costs that potentially can be estimated given different degrees of data availability. The paper argues strongly for a focus on estimating impacts on productivity, which is a key driver of economic growth. It also calls for committed action by both national governments and The World Bank Group in terms of integrating IPV and violence against women and girls (VAWG) into national and sectoral development plans and Bank funding streams; strengthening national statistics offices to collect, manage, and analyze data on violence systematically and regularly basis; prioritizing multi-sectoral and inter-ministerial responses; and most importantly establishing a dedicated budget or funding stream for IPV and VAWG policies, programs, and interventions.